Oil Price Shocks Drive Corruption; A Bibliometric Analysis - Ashfaq, Hammad; Zafar, Mahwish; Zahid, Bilal; Khan, Hafiz Muhammad Rizwan (iRASD Journal of Economics, 2023)
The world economy has a massive range of issues, including political instability, social unrest, unchecked corruption, unemployment, extreme poverty, etc. Developed countries have the resources to control it to some extent but it is difficult to remove all evils in the economy. The oil crisis has made things worse. This study proved that the stability of institutions was directly harmed by the relationship between oil prices and corruption. It has been explained how the oil crisis has changed societal structure by interfering with daily routines, academic calendars, health care facilities, transportation systems, and educational practices. For this, we use R studio productive techniques which include two types of methods first descriptive analysis like documents, and authors. Overview while another type contains structural analysis. The statistical software tool R- package and VOS viewer are used to do all of these operations. The findings show that effective government is a key tool for long-term economic success. In addition, oil prices have a favorable long- and short-term impact on economic growth. The research found little value in the findings that supported the short-term effects of governance and corruption control. This Study offers policy recommendations for creating long-term good governance that will assist national economic growth.